Hypofractionated versus conventionally fractionated radiotherapy for patients with prostate cancer (HYPRO): acute toxicity results from a randomised non-inferiority phase 3 trial. Issue 3 (March 2015) - Aluwini, Shafak; Pos, Floris; Schimmel, Erik; van Lin, Emile; Krol, Stijn; van der Toorn, Peter Paul; de Jager, Hanja; Dirkx, Maarten; Alemayehu, Wendimagegn Ghidey; Heijmen, Ben; Incrocci, Luca
Summary: Background: In 2007, we began the randomised phase 3 multicentre HYPRO trial to investigate the effect of hypofractionated radiotherapy compared with conventionally fractionated radiotherapy on relapse-free survival in patients with prostate cancer. Here, we examine whether patients experience differences in acute gastrointestinal and genitourinary adverse effects. Methods: In this randomised non-inferiority phase 3 trial, done in seven radiotherapy centres in the Netherlands, we enrolled intermediate-risk or high-risk patients aged between 44 and 85 years with histologically confirmed stage T1b–T4 NX-0MX-0 prostate cancer, a PSA concentration of 60 ng/mL or lower, and WHO performance status of 0–2. A web-based application was used to randomly assign (1:1) patients to receive either standard fractionation with 39 fractions of 2 Gy in 8 weeks (five fractions per week) or hypofractionation with 19 fractions of 3·4 Gy in 6·5 weeks (three fractions per week). Randomisation was done with minimisation procedure, stratified by treatment centre and risk group. The primary endpoint is 5-year relapse-free survival. Here we report data for the acute toxicity outcomes: the cumulative incidence of grade 2 or worse acute and late genitourinary and gastrointestinal toxicity. Non-inferiority of hypofractionation was tested separately for genitourinary and gastrointestinal acute toxic effects, with a null hypothesis that cumulative incidences of each type of adverse event were not more than 8% higher in the hypofractionation group than in the standard fractionation group. We scored acute genitourinary and gastrointestinal toxic effects according to RTOG-EORTC criteria from both case report forms and patients' self-assessment questionnaires, at baseline, twice during radiotherapy, and 3 months after completion of radiotherapy. Analyses were done in the intention-to-treat population. Patient recruitment has been completed. This study is registered withwww.controlled-trials.com, number ISRCTN85138529. Findings: Between March 19, 2007, and Dec 3, 2010, 820 patients were randomly assigned to treatment with standard fractionation (n=410) or hypofractionation (n=410). 3 months after radiotherapy, 73 (22%) patients in the standard fractionation group and 75 (23%) patients in the hypofractionation group reported grade 2 or worse genitourinary toxicity; grade 2 or worse gastrointestinal toxicity was noted in 43 (13%) patients in the standard fractionation group and in 42 (13%) in the hypofractionation group. Grade 4 acute genitourinary toxicity was reported for two patients, one (<1%) in each group. No grade 4 acute gastrointestinal toxicities were observed. We noted no significant difference in cumulative incidence by 120 days after radiotherapy of grade 2 or worse acute genitourinary toxicity (57·8% [95% CI 52·9–62·7] in the standard fractionation group vs 60·5% (55·8–65·3) in the hypofractionation group; difference 2·7%, 90% CI −2·99 to 8·48; odds ratio [OR] 1·12, 95% CI 0·84–1·49; p=0·43). The cumulative incidence of grade 2 or worse acute gastrointestinal toxicity by 120 days after radiotherapy was higher in patients given hypofractionation (31·2% [95% CI 26·6–35·8] in the standard fractionation group vs 42·0% [37·2–46·9] in the hypofractionation group; difference 10·8%, 90% CI 5·25–16·43; OR 1·6; p=0·0015; non-inferiority not confirmed). Interpretation: Hypofractionated radiotherapy was not non-inferior to standard fractionated radiotherapy in terms of acute genitourinary and gastrointestinal toxicity for men with intermediate-risk and high-risk prostate cancer. In fact, the cumulative incidence of grade 2 or worse acute gastrointestinal toxicity was significantly higher in patients given hypofractionation than in those given standard fractionated radiotherapy. Patients remain in follow-up for efficacy endpoints. Funding: The Dutch Cancer Society.